2011
DOI: 10.1177/0748233710388451
|View full text |Cite
|
Sign up to set email alerts
|

Chelation of cadmium by combining deferasirox and deferiprone in rats

Abstract: The present research aimed to characterize the potential efficiency of two chelators after cadmium administration for 60 days following two dose levels of 20 and 40 mg/kg body weight daily to male rats. However, the hypothesis that the two chelators might be more efficient as combined therapy than as single therapy in removing cadmium from the body was considered. In this way, two known chelators deferasirox and deferiprone (L(1)) were chosen and tested in the acute rat model. Two chelators were given orally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…From pervious results that reported by Fatemi. Amiri et al (2007); Tubafard and Fatemi (2008) and Fatemi et al (2011; and our present results, it can be concluded that two chelators (DFX+ DFO) are more effective as combined therapy than single therapy in removal of lead from the body. Therefore, DFX +DFO combination seems to be a promising drug of lead-mobilizing agent.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…From pervious results that reported by Fatemi. Amiri et al (2007); Tubafard and Fatemi (2008) and Fatemi et al (2011; and our present results, it can be concluded that two chelators (DFX+ DFO) are more effective as combined therapy than single therapy in removal of lead from the body. Therefore, DFX +DFO combination seems to be a promising drug of lead-mobilizing agent.…”
Section: Resultssupporting
confidence: 72%
“…Recent studies with chelators that have different lipophilic properties as combined therapy have shown favorable efficacy to mobilize mercury and cadmium (Tubafard et al, 2010). Results of this kind of combined chelation therapy has been proved by Fatemi et al (2009); Amiri et al (2007); Tubafard and Fatemi (2008); Tubafard et al (2010); Fatemi et al, (2011; and Iranmanesh et al (2013). The aim of this study was to investigate the chelating potency of DFX and DFO.…”
Section: Ajptmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, iron concentration after chelation therapy significantly increased, and returned to its normal state. From previous studies ( 26 29 ) and trial results, it can be concluded that the two chelators (DFX + L1) were more effective as a combined therapy than as single-agent therapies in the removal of thallium from the body. Therefore, the DFX + L1 combination can be considered for preliminary testing as chelation therapy in thallium toxicity cases.…”
Section: Discussionmentioning
confidence: 97%
“…Given that the risk of human exposure to Cd is persistently growing due to its prevalence in the environment and the absence of decomposable processes [34], there is a strong impetus to develop effective therapeutic strategies for managing Cd toxicity. While there is no consensus on the efficiency of chelating therapy for Cd induced toxicity, some scholars hold the view that Cd chelation may well intensify its elimination, thus reducing its toxic effects [35,36]. Interestingly, the co-administration of chelating agents and antioxidants has been associated with better effects compared to administration of each molecule individually [37].…”
Section: Discussionmentioning
confidence: 99%